2004
DOI: 10.1007/s10038-003-0116-1
|View full text |Cite
|
Sign up to set email alerts
|

Leigh syndrome caused by mitochondrial DNA G13513A mutation: frequency and clinical features in Japan

Abstract: The mitochondrial DNA (mtDNA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 33 publications
4
53
0
Order By: Relevance
“…A Japanese group detected the m.13513G4A transition in six of 84 patients with clinically LS (7.1%), but they found no complex I deficiency in the four young patients in whom this was measured. 9 All 12 other mutation positive cases reported in the literature in whom complex I activity was assessed, indeed showed reduced activity. 2 -8,10 Our study shows that the mutation is not as frequent as previously suggested and is most likely to be present in the group of patients with LS together with a complex I deficiency.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A Japanese group detected the m.13513G4A transition in six of 84 patients with clinically LS (7.1%), but they found no complex I deficiency in the four young patients in whom this was measured. 9 All 12 other mutation positive cases reported in the literature in whom complex I activity was assessed, indeed showed reduced activity. 2 -8,10 Our study shows that the mutation is not as frequent as previously suggested and is most likely to be present in the group of patients with LS together with a complex I deficiency.…”
Section: Discussionmentioning
confidence: 93%
“…Several authors have postulated that the m.13513G4A mutation is a frequent cause of either LS or MELAS and suggested that it should be routinely tested in these patients 3 -6,9,11 even in the absence of a biochemical complex I deficiency. 9,11 The objective of the current study was to determine the frequency of the mutation in a large cohort consisting of 123 patients with an established reduction in complex I enzyme activity. In addition, we review the clinical presentation of the m.13513G4A transition and discuss in which patients it is indicated for a routine molecular diagnostic laboratory, to screen for this mutation.…”
Section: Introductionmentioning
confidence: 99%
“…The m.13513AϾG transition in the ND5 gene changes an amino acid strongly conserved over 11 species (Table 1) and has been related to MELAS and Leigh syndrome in several reports. [23][24][25][26][27][28] The pathogenicity score for this mutation is 39. 22 The functional importance of this amino acid is further supported by the finding of a pathogenic mutation m.13514AϾG, affecting the same codon, that results in a different amino acid replacement (D393G vs. D393N) in two MELAS patients.…”
Section: Mtdna Variations In 28 Clinical Samplesmentioning
confidence: 99%
“…In adults, mtDNA mutations have an overall prevalence of 6.57/100,000 (6). This can result in myopathies or clinical pathologies, such as hypertrophic cardiomyopathy (HCM) (15,43) and Leigh's syndrome (LS) (45). These mutations arise more frequently in mtDNA since this genome is more susceptible to damage compared with nDNA.…”
mentioning
confidence: 99%